Performance Studies of Three-Phase Cascaded H-Bridge and Diode-Clamped Multilevel inverters (International Journal of Engineering and Computer Science, 2014)
This paper discusses a concept of two types multilevelinverters including of Cascaded H-Bridge and Diode-Clampedfor harmonic reduction on high power applications. Normally,multilevel inverters can be used to reduce the harmonic problemsin electrical distribution systems. These studies focused on theperformance and analysis of a three phase multilevel invertersincluding Cascaded H-Bridge and Diode Clamp based on SPWMapproaches. Based on the various simulations on nine levels ofmultilevel inverters, we found that the Total HarmonicsDistortion for voltage (THDV) output for both multilevelinverters is decreased. It also produces lower contents based onthe IEC standard.